Experimental Comparison of the Bearing Capacity of GFRP Beams and 50% Recycled GFRP Beams - Aleksandar Jurić; Tihomir Štefić (Civil Engineering Journal, 2022)
This manuscript investigates the possibility of using recycled glass fiber-reinforced polymer for the production of load-bearing elements in construction. Due to the increasing use of GFRP in the world, an increasing amount of waste is generated. The main objective of this research is to expand the use of composite materials in construction and, in particular, to examine the possibilities of original and recycled GFRP. Firstly, the basic characteristics of two different but very similar materials were determined using standard testing samples. Subsequently, experimental beam models were tested as a four-point bending beam model. The beam models used in this experiment were made of two types of materials, glass fiber reinforced polymer (GFRP) and recycled glass fiber-reinforced polymer (RGFRP). The experiments were conducted until the failure of the beam models. The test results are presented in the form of a force/displacement diagram, and the confirmation of the experimental results is shown by means of a numerical model of the beam. Both materials exhibited a very good strength-to-weight ratio, rendering them a suitable choice of material for load-bearing beam elements. Finally, the justification for recycling and the comparison of original and recycled material are presented in a dimensionless diagram. The comparison of these two materials provides some good insights for future research into GFRP beams. Doi: 10.28991/CEJ-2022-08-12-017 Full Text: PDF